Intraoperative vasopressors in head and neck free flap reconstruction. Issue 1 (10th November 2020) - Taylor, Robert J.; Patel, Rusha; Wolf, Bethany J.; Stoll, William D.; Hornig, Joshua D.; Skoner, Judith M.; Hand, William R.; Day, Terry A.
Abstract: Introduction: Historically, there were concerns vasopressors impair free flap outcomes, but recent studies suggest vasopressors are safe. Here we investigate this controversy by (1) evaluating vasopressors' effect on head and neck free‐flap survival and surgical complications, and (2) performing soft tissue and bony subset analysis. Patients and methods: Post hoc analysis was performed of a single‐blinded, prospective, randomized clinical trial at a tertiary care academic medical center involving patients ≥18 years old undergoing head and neck free flap reconstruction over a 16‐month period. Patients were excluded if factors prevented accurate FloTrac™ use. Patients were randomized to traditional volume‐based support, or goal‐directed support including vasopressor use. Primary data was obtained by study personnel through intraoperative data recording and postoperative medical record review. Results: Forty‐one and 38 patients were randomized to traditional and pressor‐based algorithms, respectively. Flap survival was 95% (75/79). There was no significant difference between the pressor‐based and traditional protocols' flap failure (1/38 [3%] vs. 3/41 [7%], RR 0.36, 95% CI of RR 0.04–3.31, p = .63) or flap‐related complications (12/38 [32%] vs. 18/41 [44%], RR 0.72, 95% CI 0.40–1.29, p = .36) Soft tissue flaps had surgical complication rates of 12/30 (40%) and 9/27 (33%) for traditional and pressor‐based protocols, respectively. Bony flaps had surgical complication rates of 6/11 (55%), and 3/11 (27%) for traditional and pressor‐based protocols, respectively. Conclusions: Intraoperative goal‐directed vasopressor administration during head and neck free flap reconstruction does not appear to increase the rate of flap complications or failures.